Evaluation of chromium concentration in cattle feces using different acid digestion and spectrophotometric quantification techniques - N.K.P. Souza (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2013)
The objective of this work was to evaluate combinations between acid digestion techniques and spectrophotometric quantification to measure chromium concentration in cattle feces. Digestion techniques were evaluated based on the use of nitric and perchloric acids, sulfuric and perchloric acids, and phosphoric acid. The chromium quantification in the solutions was performed by colorimetry and by atomic absorption spectrophotometry (AAS). When AAS was used, the addition of calcium chloride to the solutions as a releasing agent was also evaluated. Several standard samples containing known chromium contents were produced (0, 2, 4, 6, 8 and 10g of chromium per kg of feces) using cattle feces obtained from three different animals to evaluate the accuracy of the different combinations of techniques. The accuracy was evaluated by adjusting a simple linear regression model of the estimated values on the actual values of chromium content in the standard samples. Regardless of the digestion technique, the chromium content estimates in the standard samples obtained by colorimetry were not accurate (P<0.05). Considering the AAS quantification, the digestion techniques based on nitric and perchloric acids and based on sulfuric and perchloric acids provided complete chromium recovery (P>0.05). The use of the digestion technique in phosphoric acid provided incomplete recovery of the fecal chromium (P<0.05). Subsequently, the digestion techniques in nitric and perchloric acids and digestion in sulfuric and perchloric acids, both evaluated by AAS, were compared using 84 cattle feces samples. The results indicate that these techniques provide similar (P>0.05) fecal chromium contents.